Preoperative design of flap based on computer-aided design technology: morphological flattening and analysis of three-dimensional wound. Issue 10 (27th July 2022) - Ji, Xiaogang; Luan, Yuhao; Gong, Hao; Duan, Yushun; Zhang, Jianan; Deng, Lin
Abstract: The shape of skin flaps is only described by swatches for preoperative design because of the irregular shape of skin wounds caused by trauma in the clinic. The method is rough, and the flaps cut often cannot match the wounds and affect their appearance. Computer-aided design technology helps to attain precise results in less time. This study proposes a skin wound morphological flattening algorithm based on hierarchical values. First, the skin wound is scanned by three-dimensional (3D) scanning technology to obtain a spatial mesh model consisting of triangular cells, and the mesh model is layered with a hierarchical value. Then, the layered mesh is topologically mapped to the plane. Subsequently, the stress and strain of the skin are simulated using a mechanical method, and the shape of the flattened skin wound is optimized layer by layer. Finally, the multiresolution smoothing technique is used to smooth the developed boundary contour and fit the curve to obtain a guidance plan for preoperative flap design. The results of the study showed that this method can accurately determine the shape of the skin wounds and quantitatively analyze the preoperative design results of the skin flaps. The average error of the area and edge length after flattening was reduced to less than 10%. The work is designed to realize the precise and individualized design of flap schemes before operation and to help standardize the preoperative design process.